Analysis of positive international experience in combating human trafficking with the help of the GRETA tool - Migalchan, Alisa-Tetiana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article presents results of an analysis of Romanian and Moldova experience in combating trafficking in human beings, which was covered in the GRETA’s Compendium of good practices on the implementation of the Council of Europe Convention on Action against Trafficking in Human Beings. GRETA is a Council of Europe monitoring body, designed to assist states in combating human trafficking. For some time now Ukraine is under special supervision of this organization, especially considering its political and economic situation. GRETA visits member states of the Council of Europe Convention on Action against Trafficking in Human Beings and assesses the state of affairs and measures taken by States to prevent trafficking in human beings. The analysis of best practices allows to identify areas in the fight against the crime of trafficking in persons, which need improvement in Ukraine by amending the existing national legislation or improving administrative practices of public authorities.